2013
DOI: 10.1097/igc.0b013e3182959053
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Subsequent Malignancies in Women With Uterine Papillary Serous or Clear Cell Endometrial Cancers

Abstract: This is the first large population-based analysis of second primary malignancies after type II endometrial cancers. Uterine papillary serous carcinoma is associated with increased risks of certain subsequent malignancies, and providers should be aware of these when following up patients with this diagnosis, especially those with stage I disease. In contrast, no such associations were found with CC in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
4
1
Order By: Relevance
“…Survival is stage-related, and as would be expected, the overall 5-year survival rates of type II cancers are lower: 53% for papillary serous carcinomas and 62% for clear cell carcinomas. This is in contrast to the 83% overall 5-year survival rate for type I cancers (9). In our study, 5-year LRC, DFS, and OS rates were found to be 92.3%, 68.2% and 78.6%, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…Survival is stage-related, and as would be expected, the overall 5-year survival rates of type II cancers are lower: 53% for papillary serous carcinomas and 62% for clear cell carcinomas. This is in contrast to the 83% overall 5-year survival rate for type I cancers (9). In our study, 5-year LRC, DFS, and OS rates were found to be 92.3%, 68.2% and 78.6%, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…Few other studies have examined SPC risk according to the histological subtype of the primary EC. Hinshaw and colleagues explored site-specific SPCs among women diagnosed with serous or clear cell EC [13]. Increased risks of colorectal, renal, bladder, AML and soft tissue SPCs were observed among serous EC patients (n=8,045), whereas women with clear cell EC (n=1,740) did not experience increased SPC risk at any anatomical site.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,18 To our knowledge, this is the first population-based study investigating concordant endometrioid histology for first endometrial cancer and second ovarian cancer, but not for other histopathological subtypes. 16 Epidemiologically obesity is associated with increased risks for endometrial endometrioid carcinoma. The etiology is commonly interpreted as "unopposed estrogen" hypothesis, i.e., endometrial cancer may develop as a result of the mitogenic effects of estrogens, when these are insufficiently counterbalanced by progesterone 2 ; in another words, obesity is associated with higher levels of circulating estrogens in relation to progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous sensitivity analyses showed risk estimates of SPCs to be very similar when these registries were excluded from the analyses. 16 We therefore included all 12 registries in all analyses in order to ensure the maximum possible sample size.…”
Section: Statistical Analysesmentioning
confidence: 99%